Dynamic Change of Technical and Digital Competencies of Czech Teachers Between The First And Second Waves of The Covid-19 Pandemic - Radim ŠTĚPÁNEK; Veronika ŠVRČINOVÁ; Svatopluk SLOVÁK; Pavel DOSTÁL (Communications of International Proceedings, 2021)
The presented article evaluates selected aspects of dynamic changes in the technical and digital competencies of Czech teachers between the first and second wave of the Covid-19 pandemic (September 2020 - March 2021). Speaking at the level of acquiring new transferable technical and digital competencies of teachers in the sense of ECDL - Digital Awareness, Literacy, Competence and Expertise - these are a key determinant for an individual's ability to effectively acquire new or deeper specific and non-transferable digital competencies. Especially during the Covid-19 pandemic, the acquisition of the skills needed for working with new or specialized programs or techniques is considered crucial for the population of Czech teachers. Emphasis on understanding new technologies in context, overcoming existing preconcepts, the ability to self-educate and be able to pass on these skills was examined in a representative sample of 415 primary and secondary school teachers in the Czech Republic.
Keywords: Covid-19; Distance learning; Digital Competencies; Education; Online Teaching.